Glimt af nordisk musikvidenskab i første halvdel af det 20. århundrede : Knud Jeppesens brevvekslinger som kilder og kontekst - Holme, Thomas (Svensk tidskrift för musikforskning / Swedish Journal of Music Research, 2020)
In the Nordic countries Denmark, Finland, Norway and Sweden musicology as a research discipline was established during the first decades of the 20th century. The renowned Danish scholar Knud Jeppesen (1892–1974) – who belonged to the second of the two generations of musicologists that are outlined in the article – corresponded with a number of his Nordic colleagues, especially during the interwar period. These correspondences, all in all counting around 200 letters, form the primary source material for the article. The letter exchanges are very different as to their size, content, degree of completeness, and so on. Nevertheless, they contribute with valuable information regarding a number of issues pertaining to the upstart of Nordic musicology. Thus, the correspondences cast light on the earliest international involvements of Nordic scholars, for instance in Internationale Gesellschaft für Musikwissenschaft, the difficulties in establishing musicology as a university discipline, and the earliest organisational endeavours as to establishing a Nordic conference. The planning of such an event began already around 1930 but it was not until 1948 that the first Nordic Musicological Congress was held.